Role Of Electronic Human Resource Management in Enhancing Strategic Agility - Ali Naji, Haider; Ahmed Abdullah Amanah (Iraqi Journal for Administrative Sciences, 2024)
The research explores the role of Electronic Human Resource Management (e-HRM) in enhancing strategic agility by analyzing their relationship. The study aims to understand the role of e-HRM and its correlation with strategic agility to assist the management of the University of Karbala in enhancing performance. The problem lies in the challenges faced in achieving agility in an increasingly complex competitive environment, which may require the use of modern technology for HR management. The research was conducted at the University of Karbala, gathering opinions from directors across 17 faculties through purposive sampling. The researcher employed various statistical methods, such as mean, standard deviation, correlation analysis, and structural equation modeling, with results indicating a significant positive relationship between e-HRM and strategic agility. The study recommends increasing focus on e-HRM dimensions to enhance success and innovation in a growing competitive environment